P2 Characterisation Of Aδ- And C-fibres Innervating Guinea-pig Airways. (10th November 2014) - Adcock, JJ; Birrell, MA; Maher, SA; Bonvini, SJ; Dubuis, ED; Wortley, MA; Baker, KE; Belvisi, MG
Abstract : Introduction and objectives: Activation of afferent fibres from the lungs are involved in the cough reflex. In vitro studies in guinea-pig have demonstrated that there are various sub-types of Aδ-fibres (RAR's, nociceptive and cough) 1 and C-fibres (either nodose or jugular ganglia derived), 1, 2 however, little is known about their equivalent characteristics in vivo . This study aims to characterise the responsiveness of airway sensory nerves, in vivo, ultimately providing a better insight into understanding the role/contribution of the various types/subtypes of Aδ and C-fibres in airway reflexes such as cough. Methods: Male guinea-pigs were anaesthetized with urethane (i.p. 1.5 g kg -1 ), paralysed and artificially ventilated via a tracheal cannula. A vagus nerve was isolated: single fibres were identified as originating from Aδ- and C-fibres using several criteria. Action potentials were recorded 3 and agents were administered to the airways by aerosol. Results: Fibre-types were classified according to their conduction velocities (Table 1 ). All C-fibres examined were activated by capsaicin, whereas in the Aδ-fibres studies there were both capsaicin responsive and non-responsive fibres, irrespective of their CV range. All fibres exposed to CA responded strongly. There were marked differences in the responsiveness to the TRPV4 agonist, GSK1016790A: Aδ-fibres from all subgroups responded vigorously, but the C-fibres examined were not activated. Interestingly, administration of hypotonic solutions activated all of the Aδ-fibres, but had no effect on C-fibres. In contrast, all C-fibres responded to the TRPA1 agonist, acrolein, with no effect on Aδ-fibres. Conclusion: Several vagalafferent nerve subtypes have been identified in guinea-pig airways in vivo, although the classification does not appear as obvious to that observed in vitro . It is clear that there is a marked variation in their sensitivity to TRP channel agonists, TRPV1, TRPA1 and TRPV4, which have all been shown to evoke cough in a preclinical model in conscious guinea-pigs. It seems probable, therefore, that the different afferent pathways all regulate cough to a greater or lesser degree depending on the nature of the stimulus and underlying cause of the cough. References: Canning 2004: J Physiol- 557 (2):543–558 Weigand 2012: J Physiol- 590, (16):4109–4120 Adcock 2003: Brit J Pharmacol- 138:407–416